The Effect Of The Modified Cort Programme In Enhancing Critical Thinking And Improving Motivation To Learn Among Students With Learning Difficulties In Mathematics - Melhem, Tareq Y. M (2014)

(untitled)
The purposes of this study were to construct a training programme based on the CoRT programme and to measure its effects in enhancing critical thinking (CT) and improving motivation to learn for sixth grade student with Learning Difficulties (LDs) in mathematics in Jordan. Tujuan kajian ini adalah untuk membina satu program latihan berdasarkan program CoRT dan menilai keberkesanannya dalam meningkatkan pemikiran kritikal dan motivasi untuk belajar bagi pelajar tahun enam yang mempunyai masalah pembelajaran dalam subjek matematik di Jordan.